UNDERSTANDING NARRATIVE TEXT BY MEANS OF HERRINGBONE TECHNIQUE: EFL STUDENTS’ LEARNING EXPERIENCES AND PERSPECTIVES - Ai Tasya Wulan Dini (Journal of English Education Program (JEEP), 2020)
This article investigates EFL students’ experiences and perspectives in understanding narrative text by means of Herringbone technique. Herringbone is a kind of graphic organizers technique in teaching reading. In accordance with Rhalmi (2017, p.16), graphic organizers is one of teaching reading technique that used to help students construct meaning and visualize how ideas fit together. In this research, Herringbone technique was investigated to know about students’ learning experiences and perspectives in the implementation of it. Qualitative research was method chosen to be used with case study by using multiple instruments or triangulation as data collection techniques there are questionnaire, students’ work, and students’ reflective journal. Questionnaire was analyzed by describing and drawing the conclusion, students’ work was analyzed by checking the students’ answer, and students’ reflective journal was analyzed by describing and drawing the conclusion. In this regard, the participants in this study were twelve students which consisted of six male and six female in one of Islamic junior high schools in Tasikmalaya. In the finding of this study, researcher concludes that the most interesting students’ experiences it were caused by technical factor (group discussion and fishbone diagram). Then, almost all of student (96% students) agreed that by strengthening groups’ discussion and ask a teacher help was the solution to overcome the problem they face during learning process. Lastly, based on students’ perspective, most of students argued if Herringbone technique is success to motivate and help them to understand the text they learnt. The used of Herringbone technique made the students enjoy in learning material of reading narrative text. Finally, a suggestion has been provided for future researchers can develop this study by examining the use of this technique at higher level of education and analyze the students’ perspectives on the use of the technique with different of material. Keywords: Teaching reading technique, Herringbone technique, Narrative text, Perspective.